Pola Pengembangan Pariwisata Berkelanjutan Dengan Pendekatan Pemberdayaan Masyarakat Pada Objek Wisata Pantai Carocok Painan Kabupaten Pesisir Selatan - Ezizwita, Ezizwita; Srihasnita, Rita; Maivalinda, Maivalinda; Firsta, Firsta; Putri, Nesia Hani; Zetri, Rivaldo (Universitas Dharma Andalas, 2024)
Tourism is a significant source of revenue in many countries, including Indonesia, offering a solution to alleviate poverty. Exploring the potential and challenges of tourism management is crucial to develop a tourism model that benefits local communities. Sustainable tourism concepts are essential for ensuring visitor comfort while preserving natural and cultural heritage. Sustainable tourism also aims to boost local economies by creating job opportunities. This study analyzes the sustainable tourism development pattern at Carocok Beach, South Coastal Regency, focusing on community empowerment to enhance local economic prosperity. Employing a qualitative descriptive approach, data is gathered from literature, local communities, visitors, and relevant authorities. Findings indicate that local government plays a dominant role in developing attractions, facilities, and access to Carocok Beach. However, community participation in planning, implementation, and monitoring remains low. While the government has made strides in enhancing tourism image and supporting community development, involvement of grassroots organizations like NGOs and local cooperatives is lacking, hindering comprehensive community empowerment and economic growth Abstrak Pariwisata merupakan salah satu sumber pendapatan utama di berbagai negara, termasuk Indonesia, yang dapat menjadi solusi mengatasi kemiskinan. Oleh karena itu, diperlukan eksplorasi potensi dan kendala dalam pengelolaan pariwisata untuk mengembangkan model pengembangan pariwisata yang memberikan kesejahteraan bagi masyarakat sekitar. Implementasi konsep pariwisata berkelanjutan penting untuk menjaga kelestarian alam, budaya, dan lingkungan serta meningkatkan perekonomian lokal dengan menciptakan lapangan kerja. Penelitian ini bertujuan untuk menganalisis pola pengembangan pariwisata berkelanjutan di Pantai Carocok, Kabupaten Pesisir Selatan, dengan pendekatan pemberdayaan masyarakat guna meningkatkan perekonomian dan pendapatan mereka. Penelitian ini menggunakan pendekatan deskriptif kualitatif berdasarkan studi literatur dan informasi dari masyarakat, pengunjung, dan instansi terkait. Hasil penelitian menunjukkan dominasi peran Pemerintah Daerah dalam pengembangan atraksi, fasilitas, dan akses wisata di Pantai Carocok. Namun, partisipasi masyarakat dalam perencanaan, pelaksanaan, dan pengawasan masih rendah, sementara peran pemerintah dalam melibatkan organisasi masyarakat belum optimal.